Bibliometric analysis of RNA vaccines for cancer - Xue Yang; Jian Kang; Zhaohui Xing; Yongtao Sun; Zhipeng Liu; Nannan Li; Jirui Niu (Taylor & Francis Group, 2023)
Cancer represents a challenging medical problem worldwide. Several exploratory studies have been conducted to overcome these limitations. RNA vaccines play an important role in cancer prevention and treatment. Recent studies have shown that RNA vaccines play an important role in cancer prevention. However, there are currently no relevant bibliometric studies. This study aimed to apply bibliometrics to summarize the knowledge structure and research hotspots regarding the role of RNA vaccines in cancer. Publications related to RNA vaccines in cancer were searched on the web of science core collection (WoSCC) database. VOSviewers, CiteSpace and R package "bibliometrix" were used to conduct this bibliometric analysis. A total of 1399 articles were included, comprising 803 original articles and 596 reviews. The number of studies on RNA vaccines against cancer has been increasing annually. China and the United States were the principal countries of origin of publications. Johannes Gutenberg University Mainz, NCI, and Duke University were the main organizations. Frontiers in Immunology is the leading journal in the field. Hot keywords included tumor antigens, lipid nanoparticles, emerging roles, and dendritic cells. This is the bibliometric study to summarize the research trends and development of RNA vaccines for cancer. This information will provide a reference for researchers studying RNA vaccines against cancer.